Secretory Leukocyte Protease Inhibitor in Preterm Labor and Pregnancy: Secretory Leukocyte Protease Inhibitor pada Persalinan dan Kehamilan Prematur - Ferriyanto Sutiono; Juneke J Kaeng; Maria FT Loho (Indonesian Journal of Obstetrics and Gynecology, 2018)
Objective: To investigate the levels of secretory leukocyteprotease inhibitor (SLPI) in women with preterm labor andpregnancy. Methods: SLPI level examination conducted to 32 samples ofpregnant women who meet the inclusion and exclusion criteria,consists of 16 preterm labor and 16 preterm pregnancy.Sample analysis carried out in Prodia Laboratory Jakarta. SLPIlevel examination used ELISA method. The obtained dataprocessed by SPSS software version 20.0 and discussed withexisting literature theory. Results: Mean plasma SLPI level in patients with preterm laboris 30.319 ng/ml and median: 29.950 ng/ml with p value: 0.652,while the mean on preterm pregnancy is 45.975 ng/ml andmedian: 41.600 ng/ml with p value: 0.005. Conclusion: There are significant differences of SLPI level betweenpreterm labor and preterm pregnancy. Keywords: preterm labor, preterm pregnancy, SLPI